2018
DOI: 10.1002/alr.22132
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing the supraglottic airway to use of an endotracheal tube in sinonasal surgery

Abstract: While the use of the SGA results in patient diet modification postoperatively, it may also be associated with a reduction in throat pain and dysphonia. SGA use had no appreciable effect on postanesthesia recovery times, oxygen desaturations, or emesis. Use of the SGA in sinonasal surgery appears to be a safe and reliable option for airway management in selected adult patients undergoing routine ambulatory sinonasal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In a number of institutions, endoscopic sinus surgery (ESS) is performed with a supraglottic airway (SGA) rather than with endotracheal intubation (ETT) although airway protection in the potentially bloody environment of sinus surgery has been a very real concern. A randomized single‐blind study in this issue of the Journal by Adams et al . demonstrates equal airway protection with SGA and ETT in sinus surgery.…”
mentioning
confidence: 93%
“…In a number of institutions, endoscopic sinus surgery (ESS) is performed with a supraglottic airway (SGA) rather than with endotracheal intubation (ETT) although airway protection in the potentially bloody environment of sinus surgery has been a very real concern. A randomized single‐blind study in this issue of the Journal by Adams et al . demonstrates equal airway protection with SGA and ETT in sinus surgery.…”
mentioning
confidence: 93%
“…Accordingly, many anaesthesiologists and otolaryngologists are reluctant to use FLMA in FESS. However, several prospective trials have indicated that FLMA effectively protects the airway from blood contamination during FESS, showing superiority in protecting the glottis and subglottic airway [5,6]. Other concerns are related to the failure rate of FLMA ventilation, which can occur because, compared with other types of LMA, the elasticity of its tube makes it more difficult to insert and align accurately.…”
Section: Introductionmentioning
confidence: 99%